Analysis of Factors Affecting the Level of Credit Distribution - Azasi Hasan; Sidik Priadana; Pudji Astuty (Interdiciplinary Journal and Hummanity (INJURITY), 2023)
The success of economic development in Indonesia will depend on the role of banks in providing financial services that can encourage increased economic activity to achieve successful growth in various sectors. This study aims to determine and examine the magnitude of the effect of inflation, bank interest, promotions, information technology, third-party funds, and SBI rates on the credit distribution of commercial banks that go public. The study uses a descriptive and verification approach by analyzing Time Series data over 20 years period. The analysis method in this study uses multiple regression analysis. There is a positive and significant effect of the variables of Inflation, Bank Interest, Promotion, Information Technology, Third Party Funds, and SBI rates simultaneously on credit where the six independent variables are the dominant variables that form credit together. There are positive and negative and significant effects of each variable Inflation, Bank Interest, Promotion, Information Technology, Third Party Funds, and SBI rates on credit. The variable that has the biggest influence on credit is the Promotion variable, while the variable with the smallest absolute influence on credit is Bank Interest. All models in this study obtained both positive and negative and significant results.